Efficient model and feature selection for SVM in biomedical data analysis - Zhao, Ying. (2008)
In this thesi, we proposed to improve the model selection techniques for L2-SVMs and LS-SVMs. A new feature seletion algorithm is also proposed for LS-SVMs.